Sosialisasi Kepada Masyarakat Tentang Bijak dalam Mengkonsumsi Obat Pada Lansia di Kecamatan Tanjung Pura Kabupaten Langkat - Dhea Nur Fadhilah; Manahan Situmorang; Dumartina Hutauruk; Julia Susanti (Universitas Kristen Indonesia Toraja, 2023)
Elderly is an age group in humans who have entered the final stages of their life phase. The group that is categorized as elderly will experience a process called the aging process. Indonesia is entering a period of aging population, where there is an increase in life expectancy followed by an increase in the number of elderly people. In Indonesia, there has been an increase in the number of elderly people from 18 million people (7.56%) in 2010 to 25.9 million people (9.7%) in 2019, and can be expected to continue to increase where in 2035 it will be 48.2 million people (15.77%). On the other hand, an increase in the number of elderly people will be a problem if the elderly have health problems. The elderly are a group of people who are susceptible to disease and have different physiological functions from young people, so their treatment pattern becomes more careful. The purpose of this community service activity is to provide outreach and information to the public about the proper and correct use of drugs in Tanjung Pura District, Langkat Regency regarding Provision of Drug and Wise Information on the proper and correct use of drugs. The method of this activity involved the community in Tanjung Pura District, Langkat Regency, namely lectures, distribution of leaflets, and questions and answers. Lectures are presented in the form of power point presentations, distribution of leaflets in the form of brochures followed by a discussion or question and answer session about Wisdom in taking medicine in the elderly. The result of this activity is that in Tanjung Pura District, Langkat Regency understand and are wise in taking drugs, especially in the elderly.